Ray City Community News. Vol. 1, No. 3, October - December, 1990 - Ray City Community Library (Ray City Community Development Council, 1990)
Ray City Community News. Vol. 1, no. 3 (October - December 1990). Ray City Community Development Council. CA014-001: Ray City Community Library, 1952–1994 Series. Ray City Community Library Collection.
Ray City Community News. Vol. 1, no. 3 (October - December 1990). 1 electronic record (PDF), 2.00 MB (2,097,171 bytes), 5 scans, 8 pages.
Keywords: Electronic records; Ray City (Ga.); Berrien County (Ga.); Newsletters; Periodicals